Rural Descriphons in Eighteenth-Centory Poem: Thomson Goldsmith, Crabbe, Donelaiiis - Kuosaitė, Elena (Literatūra, 1972)
Thomson’s poem „The Seasons", Goldsmith’s „The Deserted Village", Crabbe’s „The Village", and Donelaitis’ „The Seasons" are linked by the common theme of rural life. Thomson was the initiator of eighteenth-century rural poetry. Only several scenes of country life are presented in his poem which is devoted mostly to natural description, moral and philosophical considerations. Goldsmith was interested in the first place to convey the spirit of regret over the changes that were taking place in the English village. The focus of his attention was concentrated on the idyllic picture of the village in the past. Crabbe saw only the dark sides of village life and portrayed a dismal picture of rustic world in his poem. Donelaitis gives a full and realistic picture of country life. The poet presents many scenes of everyday life and the farmers’ labour, describes their customs and recreations, portrays the colourful figures of the boors. The author reveals the controversies of country life engendered by social as well as moral motives. The poems of the authors in review are distinguished by their social implications. In Thomson they are expressed in a more abstract form, as a contrast between the village and the city between luxury and poverty. In Goldsmith, Crabbe and Donelaitis they acquire a more concrete historical form. Goldsmith and Crabbe revealed the contradictions brought into the English village by the development of capitalist relations, while Donelaitis presented contradictions characteristic of the feudal system. The poems presenting different aspects of country life differ from each other in their stylistic qualities. It is characteristic of Thomson to use high-flown imagery and an elevated diction which in part is a characteristic feature of Goldsmith’s poem too. But in Goldsmith alongside of the idyllic pictures of the past can be found images of desolation and destruction. In the atmosphere and imagery of Crabbe’s poem there is a sense of helplessness and decay. His poem is contrasted to those of Thomson and Goldsmith. The descriptions of Donelaitis are matter-of-fact and vivid; the narrative is distinguished by variety of tone, which changes from serious to comic, from lyric to dramatic. Dialogue and direct speech adds much to the vigorous effect of the poem. The subject matter and the structural qualities of Donelaitis’ poem make him a typical figure of eighteenth century literature. But one must remember that his creative power was formed not only by literary models and authorities. It was raised and conditioned by folk tradition as well. That’s why he succeeded better in reproducing the very essence of the peasant’s nature, his psychology and his way of looking at life. And through the consciousness of the peasant he revealed some principal aspects of human existence and of his relations to nature.